2007
DOI: 10.1080/09613210600979848
|View full text |Cite
|
Sign up to set email alerts
|

Integrating disaster risk management into construction: a UK perspective

Abstract: Although most disasters are not entirely unexpected and therefore can, to varying degrees, be mitigated for, the construction sector in the UK does not play a sufficiently integrated role in disaster risk management. This paper reports on research that is developing a knowledge database and decision support framework to enable more effective disaster risk management strategies from a construction perspective. Questionnaire surveys and semi-structured interviews were used to review the opinions of professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 12 publications
4
69
0
2
Order By: Relevance
“…Though there have been many attempts to increase disaster resilience through capacity building and development initiatives, gaps in capacity are still in existence in various forms. Among such gaps identified in disaster risk reduction in the built environment are a lack of disaster management related awareness; a lack of proper education and training, and a lack of skilled and trained human resources (Bosher et al, 2007b). Therefore, these gaps indicate that 'education' is a key to addressing such capacity gaps.…”
Section: Skills and Capacities Of Built Environment Professionals In mentioning
confidence: 99%
“…Though there have been many attempts to increase disaster resilience through capacity building and development initiatives, gaps in capacity are still in existence in various forms. Among such gaps identified in disaster risk reduction in the built environment are a lack of disaster management related awareness; a lack of proper education and training, and a lack of skilled and trained human resources (Bosher et al, 2007b). Therefore, these gaps indicate that 'education' is a key to addressing such capacity gaps.…”
Section: Skills and Capacities Of Built Environment Professionals In mentioning
confidence: 99%
“…In short, the search for interprofessional solutions in resilient planning aims to facilitate a joined-up approach to development among the police, emergency planners, spatial planners and other built environment professionals through incorporating risk management into urban decision-making. 30 Similar reforms have taken place in transport operations, with an increasingly regulatory approach for both national 'heavy' rail and urban light rail or metro systems, and the publication of a recommended best practice guide for bus and coach security. 33 Development of this multi-level and inter-professional managerial nexus for resilience is still ongoing and has tended to be more concerned with developing statutory obligations than in broadening the inclusively of decision making.…”
Section: Balancing Effectiveness and Acceptability In Counter-terrorimentioning
confidence: 99%
“…Current research has identified that key stakeholders recognise that resilient design will become central to planning, construction guidelines and legislation in the near future. 30 An important aspect of counter-terrorism design is that it can provide benefits at very low cost if it is implemented at the planning stage of a shopping area, rail system or venue, 31 whereas costs can be much higher in a retro-fit situation. 32 For example, this message was reinforced by Lord West's counterterrorism report, which emphasised how proactive engineering and management solutions to mitigate the impact of terrorism should be incorporated into pre-planning and design stages of new developments.…”
Section: Beyond Engineered Defencementioning
confidence: 99%
“…Mileti (1999), Ofori (2004) and Bosher and Dainty (2011) also underline the importance of the construction sector in minimising the adverse impacts of disasters through hazard mitigation. Traditionally, two types of hazard mitigation are considered (Bosher et al, 2007b).…”
Section: Stakeholders In Drrmentioning
confidence: 99%